2005
DOI: 10.1073/pnas.0409467102
|View full text |Cite
|
Sign up to set email alerts
|

Indirubin derivatives inhibit Stat3 signaling and induce apoptosis in human cancer cells

Abstract: Stat3 protein has an important role in oncogenesis and is a promising anticancer target. Indirubin, the active component of a traditional Chinese herbal medicine, has been shown previously to inhibit cyclin-dependent kinases, resulting in cell cycle arrest. Here, we show that the indirubin derivatives E564, E728, and E804 potently block constitutive Stat3 signaling in human breast and prostate cancer cells. In addition, E804 directly inhibits Src kinase activity (IC50 ‫؍‬ 0.43 M) in an in vitro kinase assay. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
248
2
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(264 citation statements)
references
References 32 publications
8
248
2
6
Order By: Relevance
“…MSC/IFN-β inhibits 4 T1 cell proliferation in vitro It has been reported that Stat3 inhibition can induce apoptosis [36,37]. However, in our previous studies [19,20], we did not detect apoptosis after either knockdown or inhibition of Stat3.…”
Section: Ifn-β Inactivatescontrasting
confidence: 82%
“…MSC/IFN-β inhibits 4 T1 cell proliferation in vitro It has been reported that Stat3 inhibition can induce apoptosis [36,37]. However, in our previous studies [19,20], we did not detect apoptosis after either knockdown or inhibition of Stat3.…”
Section: Ifn-β Inactivatescontrasting
confidence: 82%
“…As a matter of fact, STAT3-binding motifs are present in the promoter of Mcl-1 (Puthier et al, 1999). Other studies have reported decreased Mcl-1 expression and increased apoptosis after disruption of phospho-STAT3 signaling (Niu et al, 2002;Lee et al, 2004;Nam et al, 2005). However, we can exclude an involvement of the JAK/ STAT3 pathway in the regulation of Mcl-1 in the present study, as LNCaP-IL-6 þ cells have been previously shown to lack phosphorylated STAT3 (Steiner et al, 2003).…”
Section: Discussionmentioning
confidence: 57%
“…About 5 mM indirubin-3 0 -monoxime also inhibited the phosphorylation of ERK1/ 2, PLCg, STAT1 and STAT3 in KG-1a cells. Previously, certain indirubin deratives were reported to inhibit phosphorylation of STAT3 by inhibiting an upstream kinase, Src (Nam et al, 2005). However, 5 mM indirubin-3 0 -monoxime did not inhibit phosphorylation of Src in the KG-1a cells, indicating that phosphorylation of STAT3 in this case is a downstream event to phosphorylation of the FGFR1 kinase.…”
Section: Indirubin-3 0 -Monoxime Inhibits Fgfr1mentioning
confidence: 69%
“…Furthermore, indirubin-3 0 -monoxime, but not indirubin, was able to inhibit CDK9 in a cell-free kinase assay and to inhibit replication of HIV-1 in blood mononuclear cells and macrophages (Heredia et al, 2005). Additionally, it was recently reported that indirubin derivatives were able to block Stat3 signaling by inhibiting the Src kinase activity and in this way induce apoptosis in human cancer cells (Nam et al, 2005), and also, bind to and inhibit glycogen synthetase kinase-3 (Leclerc et al, 2001;Polychronopoulos et al, 2004), aryl hydrocarbon receptor (Adachi et al, 2001), muscle glycogen phosphorylase b (Kosmopoulou et al, 2004) and c-Jun NH2-terminal kinase (JNK) (Xie et al, 2004). More recently, indirubin-3 0 -monoxime was found to inhibit the activation of nuclear factor-kB resulting in enhancement of apoptosis induced by tumor necrosis factors in human leukemic cells (Sethi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%